THE RESULTS OF THE STUDY OF VARIETIES OF ALFALFA IN THE CENTRAL-CHERNOZEM ZONE - N. I. Isaeva; N. Yu. Malysheva; L. L. Malyshev; N. V. Vavkina (Труды по прикладной ботанике, генетике и селекции)
Three-year study of one hundred world collection of alfalfa was conducted in Central Black-Earth zone of Russia. The varieties of Medicago × varia ‘Zheltogibridnaya 99’, ‘Flora 2’, ‘Karlygash’ and ‘№ 152’ (hybrid ‘Severnaya hybridnaya’ ×‘Augune II’) were recommended for breeding programs. The most variable were character of seed production, productivity of green mass and hay yield productivity; character of foliage and the intensity of regrowth of plants on the 20-th day after spring regrowth had medium variability. The height before the first mowing and height in the phase of full flowering had low variability. There was a significant correlation between the yield of green mass and hay, the yield of green mass and intensity of regrowth and a weak negative correlation between the yield of green mass and seed yield.